2021
DOI: 10.4103/jfmpc.jfmpc_1527_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence pattern of MRSA from a rural medical college of North India

Abstract: Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) has become a global challenge. The shift of this organism form hospital settings to community setting and increasing resistance to non-β-lactams antibiotics have further aggravated the crisis. This trend in MRSA has necessitated the knowledge and sensitization about this agent among physicians in rural and peripheral settings. Material and Methods: Present study was undertaken at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…26,27 However, some of the authors have observed a lower prevalence of MRSA in their study but all of them reported increasing trend of MRSA prevalence in their study. 28,29 Our study found significantly higher prevalence of Inducible…”
Section: Discussionmentioning
confidence: 51%
“…26,27 However, some of the authors have observed a lower prevalence of MRSA in their study but all of them reported increasing trend of MRSA prevalence in their study. 28,29 Our study found significantly higher prevalence of Inducible…”
Section: Discussionmentioning
confidence: 51%
“…According to a multicentric study conducted in India, the prevalence of MRSA was 41% in 2013 [19]. In another study from North India, this figure reached 33.7% between 2017 and 2019 [20]. According to the Indian Council of Medical Research (ICMR) report on antimicrobial resistance, the prevalence of MRSA in India was 38.6% in 2018 and 42.1% in 2019 [21].…”
Section: Discussionmentioning
confidence: 99%
“… 24 A study conducted in North India over a period of 3 years reported that MRSA increased from 28% in 2017 to 35.1% in 2019 with overall prevalence being 33.7%. 25 The prevalence of MRSA infection was 37.34% according to a recent meta-analysis report from South India. 26 In Asia-Pacific region, MRSA accounts for up to 50% of Staphylococcus aureus bloodstream infections.…”
Section: Discussionmentioning
confidence: 99%